An 8‐week, open‐label study to evaluate the effect of sertraline on the polysomnogram of depressive patients with insomnia. Issue 3 (22nd April 2013) - Zhang, Bin; Hao, Yanli; Li, Xueli; Ren, Yanzhen; Zhou, Ping; Liu, Wuhan
Abstract: We want to evaluate the effect of sertraline on polysomnogram (PSG) and clinical variables in depression. An 8‐week and open‐label trial ( n = 31) was applied. The primary outcome was mean baseline‐to‐visit changes in PSG variables. The secondary outcomes were clinical improvement, side‐effects, and the subjective sleepiness. Rapid eye movement (REM) latency was prolonged significantly over the course of the study. The arousal index reached the highest level on the 1st day (13.8 ± 7.2). From the 14th day onward, the sleep latency (SL) and wake after sleep onset (WASO) decreased significantly. The percentage of stage 3 sleep increased in this trial. The Hamilton Rating Scale for Depression (HRSD) and Clinical Global Impression (CGI) scores on the 14th, 28th, and 56th days were significantly lower than baseline. Furthermore, a significant correlation was shown between the decreasing score rate of HRSD on the 56th day and the decreasing score rate of REM latency on the 1st day ( r = −0.733, P = 0.003). The effectiveness of sertraline positively correlated with the reduction of REM latency. The final clinical improvement could be predicted by the extent of the prolongation of REM latency on the first night.